(untitled) (Research, Society and Development, 2021)
Develop an integrative review about orbital infection by penetrating foreign body, through the analysis of gender and most prevalent age, etiology, signs and symptoms, surgical approach and sequelae. In addition, to report a case of orbital infection by a penetrating foreign body with severe mouth opening limitation. It consists of two stages: first, two authors independently searched for articles on orbital infection by penetrating foreign bodies in the databases "MEDLINE / PubMed", "Scielo" and "Scopus ’’, using descriptors combined with the Boolean operators. The second stage consists of a case report of orbital cellulitis after penetration of a foreign body (“piece” of wood) in an orbit floor. This lesion was more common in males (75%), with an average age of 41.7 years, due to work accidents (33.3), evolving with signs and symptoms of skin lesion, pain, ophthalmoplegia, low visual acuity and abscess. The most used surgical approach is the orbitotomy (41.7%), with patients without post-surgical sequelae (50%). The case should be managed by a multidisciplinary team, with an immediate approach, avoiding the spread of infection to the intracranial region. It was also concluded that the risk of infection is directly related to the nature of the foreign body material.